2020
DOI: 10.1111/imig.12752
|View full text |Cite
|
Sign up to set email alerts
|

Labour Market Integration of Refugee Health Professionals in Germany: Challenges and Strategies

Abstract: Refugee health professionals are a vulnerable group in a host country's labour market as they experience several barriers on their path to labour market integration. This study aims to identify challenges refugee health professionals and their supervisors experience at their workplaces and strategies they have developed to overcome these barriers. Semi-structured interviews were conducted with refugee health professionals who have been living in Germany for an average of four years and their supervisors (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…Although the migration literature has indicated some possible pathways that link language to employment, it has not yet identified mechanisms or mediators to interpret how language skills can influence employment outcomes. Despite being mostly untested, migration scholars have suggested that psychological capital and resources (Newman et al, 2018a;Newman et al, 2018b;Xu et al, 2019), societal and cultural adaptability (Ravasi et al, 2015;Ryan et al, 2008), the experience of discrimination (Khan Gökkaya & Mösko, 2020;Koopmans, 2016;Syed & Murray, 2009), perceived (in)ability in matching occupational requirements (McCoy & Masuch, 2007), and health and wellbeing (Steel et al, 2015) may have a significant impact. This stream of literature underscores three critical categories of potential mechanisms, including personal psychological resources, health, and contextual/social experiences.…”
Section: Existing Literaturementioning
confidence: 99%
“…Although the migration literature has indicated some possible pathways that link language to employment, it has not yet identified mechanisms or mediators to interpret how language skills can influence employment outcomes. Despite being mostly untested, migration scholars have suggested that psychological capital and resources (Newman et al, 2018a;Newman et al, 2018b;Xu et al, 2019), societal and cultural adaptability (Ravasi et al, 2015;Ryan et al, 2008), the experience of discrimination (Khan Gökkaya & Mösko, 2020;Koopmans, 2016;Syed & Murray, 2009), perceived (in)ability in matching occupational requirements (McCoy & Masuch, 2007), and health and wellbeing (Steel et al, 2015) may have a significant impact. This stream of literature underscores three critical categories of potential mechanisms, including personal psychological resources, health, and contextual/social experiences.…”
Section: Existing Literaturementioning
confidence: 99%
“…Their research, however, shows considerable differences among Syrians in the Netherlands in terms of educational attainment, work experience before arrival, family situation and age. The authors call on policymakers to pay attention to individual needs, echoing other authors in this special issue (Ghorashi, 2020;Khan-Gökkaya & Mösko, 2020;Mozetič, 2020).…”
Section: Parti Cipati Onmentioning
confidence: 87%
“…These structural changes will be necessary to address institutional bias against highly skilled refugees in the labour market, the workplace and society at large. Khan-Gökkaya and Mösko (2020) highlight diversity management as a promising tool to create an inclusionary environment in the workplace. Institutional leaders and supervisors could use these tools to examine their own perspectives on diversity and to engage in discussions about diversity in the workplace.…”
Section: B E Yond L Abour Marke T Integ R Ation: Taking Diver S It Y and In Clus Ion Into Accountmentioning
confidence: 99%
See 2 more Smart Citations